Modeling and simulation of a Renzoku puzzle pattern-based PV array configuration for a partially shaded PV system - Aljafari, Belqasem; Balachandran, Praveen Kumar; Samithas, Devakirubakaran; Thanikanti, Sudhakar Babu; Nwulu, Nnamdi I. (Frontiers in Energy Research, 2024)
The world highly depends on electrical energy for accessing all the technologies. For the generation of electricity, technology finds a way of utilizing renewable energy sources like solar energy, and wind energy. Solar PV system occupies their space among consumers due to their feasibility, flexibility, cost, and simple implementation procedures. The solar PV system experiences many powerloss-causing factors like partial shading, hotspots, diode failure, and so on. In this work, a new static PV array configuration named Renzoku puzzle pattern-based array configuration is proposed. This proposed configuration technique was overcoming the drawbacks in the previously proposed array configurations in terms of power generation, fewer mismatch losses, high shade dispersion rate, and consistent performance under any level of partial shadings. The proposed array configuration has been validated in both simulation and hardware. The simulation is carried out in a 9×9 PV array in MATLAB/Simulink®. The performance analysis, results, and corresponding characteristic curves were presented in this manuscript.